Antiviral Action against SARS-CoV-2 of a Synthetic Peptide Based on a Novel Defensin Present in the Transcriptome of the Fire Salamander (Salamandra salamandra) - Barros, Ana Luisa A. N.; Silva, Vladimir C.; Ribeiro-Junior, Atvaldo F.; Cardoso, Miguel G.; Costa, Samuel R.; Moraes, Carolina B.; Barbosa, Cecília G.; Coleone, Alex P. [UNESP]; Simões, Rafael P. [UNESP]; Cabral, Wanessa F.; Falcão, Raul M.; Vasconcelos, Andreanne G.; et al. (MDPI, 2024)
The potential emergence of zoonotic diseases has raised significant concerns, particularly in light of the recent pandemic, emphasizing the urgent need for scientific preparedness. The bioprospection and characterization of new molecules are strategically relevant to the research and development of innovative drugs for viral and bacterial treatment and disease management. Amphibian species possess a diverse array of compounds, including antimicrobial peptides. This study identified the first bioactive peptide from Salamandra salamandra in a transcriptome analysis. The synthetic peptide sequence, which belongs to the defensin family, was characterized through MALDI TOF/TOF mass spectrometry. Molecular docking assays hypothesized the interaction between the identified peptide and the active binding site of the spike WT RBD/hACE2 complex. Although additional studies are required, the preliminary evaluation of the antiviral potential of synthetic SS-I was conducted through an in vitro cell-based SARS-CoV-2 infection assay. Additionally, the cytotoxic and hemolytic effects of the synthesized peptide were assessed. These preliminary findings highlighted the potential of SS-I as a chemical scaffold for drug development against COVID-19, hindering viral infection. The peptide demonstrated hemolytic activity while not exhibiting cytotoxicity at the antiviral concentration.
Keywords: amphibians; antimicrobial peptides; antiviral action; bioinformatics; SARS-CoV-2 infection; transcriptomics